Design of a Website-Based Point-of-Sale Information System at "Vapeboss" Vape Shop Using the Waterfall Method - Hamid Maulana Hasbi; Muhammad Rozahi Istabul (Journal of Social Research, 2023)
Vapebos is a one-stop vape shop catering to vaping enthusiasts, offering a wide array of products essential for vapers or electronic cigarette users. Their inventory spans devices like Mods, Atomizers (RDA), a diverse range of flavored liquids, and various accessories. Presently, Vapebos employs a manual transaction system where each sale is noted in a physical ledger. However, this approach poses potential issues, such as the loss of transaction records or damage due to exposure to water. To tackle these challenges and ensure smoother operations, the store is transitioning to a modernized Point of Sale (POS) system. The chosen methodology for this transformation is the waterfall-based approach. By employing the waterfall model, the authors are developing a POS application that streamlines Vapebos' transaction processes. This system promises enhanced efficiency and accuracy, reducing the likelihood of data loss or errors that might occur with the manual method. This endeavor not only aims to simplify day-to-day transactions but also contributes to maintaining a secure and organized record-keeping system. The adoption of a POS system aligns with Vapebos' objective of providing seamless service to its customers and safeguarding its business operations against potential setbacks. Through this systematic upgrade, Vapebos is poised to offer a more reliable and efficient shopping experience for vape enthusiasts while ensuring the integrity of their transaction records.